KONSELING SEBAYA SEBAGAI ALTERNATIF PENURUNAN PERILAKU PROKRASTINASI AKADEMIK [PEER COUNSELING AS AN ALTERNATIVE FOR ACADEMIC PROCRASTINATION BEHAVIOR] - Liqoiyah, Irmania; Santoso, Hardi; Sumiyem, S (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2022)
Peer counseling is an alternative approach in counseling services to help individuals carried out by peers. Peer counseling is seen as important because in today's era, individuals more often discuss the problems they face with their peers than with parents or teachers. Peer counseling makes it easier for individuals to talk more comfortably to peers. Therefore, this counseling is suitable for individuals, especially those who have Academic Procrastination Behavior. Peers who do counseling require competencies that must be possessed to support the success of counseling and create good relationships with friends. The method used in this research is a literature study by collecting various kinds of journals related to the subject of the research. The results based on this study can be concluded that peer counseling is an alternative approach that has effectiveness for individuals who have academic procrastination behavior. By using these alternatives, individuals who have Academic Procrastination Behavior have the convenience to tell stories and are able to overcome the problems they face.